The in situ local immune response, tumour senescence and proliferation in colorectal cancer - Roxburgh, C S (Nature Publishing Group, 2013)
BACKGROUND: Immune cell infiltrates are important determinants of colorectal cancer (CRC) outcome. Their presence may be driven by tumour or host-specific factors. From previous studies in mice, senescence, a state of cell cycle arrest, may moderate tumour progression through upregulation of antitumour immune responses. The relationships between senescence and immune infiltrates have not previously been studied in humans. We explore whether a marker of senescence (p16(ink4a)) in combination with low level expression of a proliferation marker (ki-67) relate to T cell infiltrates in CRC, and whether p16(ink4a), Ki-67 and immune infiltrates have similar prognostic value. METHODS: Immunostaining of p16(inka) and Ki-67 was performed within a CRC tissue microarray. Nuclear p16(inka) and Ki-67 were categorised as high/low. T-cell markers, CD3, CD45RO, CD8 and FOXP3 were scored separately as high/low grade in three areas of the tumour: the invasive margin (IM), tumour stroma and cancer cell nests (CCNs). RESULTS: Two hundred and thirty stage I–III cancers were studied. High nuclear p16(ink4a) was expressed in 63% and high proliferation (Ki-67 >15%) in 61%. p16(ink4a) expression was associated with reduced CD45RO+ cells at the IM (P<0.05) and within the stroma (P<0.05) and reduced CD8+ cells at the IM (P<0.01). A low Ki-67 proliferative index was associated with reduced density of CD3+ cells in CCNs (P<0.01), reduced CD45RO+ cells at the IM (P<0.05) and within the CCNs (P<0.001), reduced FOXP3+ cells at the IM (P<0.001), within the stroma (P=0.001) and within CCNs (P<0.001) and reduced CD8+ cells at the IM (P<0.05) and within the CCNs (P<0.05). Tumours with both a low proliferative index and expression of p16(ink4a) demonstrated similar consistent relationships with reduced densities of T-cell infiltrates. On multivariate analysis, TNM stage (P<0.001), low CD3 cells at the IM (P=0.014), low CD8 cells at the IM (P=0.037), low proliferation (Ki-67; P=0.013) and low senescence (p16(ink4a); P=0.002) were independently associated with poorer cancer survival. CONCLUSION: Senescence, proliferation and immune cell infiltrates are independent prognostic factors in CRC. Although related to survival, p16(ink4a)-associated senescence is not associated with an upregulation of antitumour T-cell responses.